Beyond adjustment: complex roles of personality and health-related strains in expatriate performance. (2016) - Ren, Hong; Harrison, David A.; Shaffer, Margaret A.; Bhaskar-Shrinivas, Purnima
We proposed and investigated the complex roles of higher order personality dimensions and health-related strains in relation to expatriate adjustment and performance using comparable cross-sectional (n = 170) and longitudinal (n = 77) samples of software engineers posted from India to North America, Western Europe and East Asia. Results indicate that social desirability personality is negatively related to heath-related strains and positively related to task performance, while superiority striving personality is positively associated with cultural adjustment. Using longitudinal data, we also clarified the temporal sequence of health-related strains relative to adjustment and performance. The results suggest that health-related strains are an important antecedent of adjustment, rather than a consequence. Also, expatriate task and relationship performance is a function of health strains and not a predictor. Overall, our findings support a multifaceted influence of dispositions and a pivotal role of health problems on international assignments.